Increased serum type I interferon activity in early systemic sclerosis patients is associated with antibodies against Sjögren's syndrome antigens and nuclear ribonucleoprotein antigens. (May 2013) - Wuttge, DM; Lood, C; Tufvesson, E; Scheja, A; Truedsson, L; Bengtsson, AA; Hesselstrand, R
<x xml:space="preserve">Abstract</x> Objective: To study serum type I interferon (IFN) activity in patients with early systemic sclerosis (SSc). Method: Serum type I IFN activity was measured in 33 consecutive patients with SSc and a disease duration of < 2 years and in 13 healthy individuals by calculating a type I IFN score according to the induction of six IFN-α regulated genes in a reporter cell line. Results: Twenty-seven per cent of the SSc patients had an increased type I IFN score compared to none of the healthy individuals (p < 0.05). The clinical SSc phenotype associated with high serum type I IFN activity did not differ from patients with low serum type I IFN activity regarding the presence of skin or lung fibrosis, pulmonary hypertension, or digital complications. Patients with high serum type I IFN activity were younger (p < 0.01) and had a lower frequency of cardiac involvement (p = 0.053), lower leucocyte count (p < 0.001), higher immunoglobulin (Ig)G levels (p < 0.05), and a higher amount of antibodies against extractable nuclear antigens (p < 0.01) than patients with low serum type I IFN activity. The presence of antibodies against topoisomerase I, Sjögren's syndrome antigen, and nuclear ribonucleoprotein antigens was associated with higher type I IFN activity (p < 0.05 for all comparisons). Conclusions: Our study indicates that increased serum type I IFN activity in early SSc patients is associated with an antibody and laboratory profile that may reflect a subclinical overlap of SSc with other type I IFN-driven connective tissue diseases (CTDs).